Advances in prostate-specific membrane antigen-targeted theranostics: from radionuclides to near-infrared fluorescence technology - Jiang, Zhongji; Kadeerhan, Gaohaer; Zhang, Jin; Guo, Wenmin; Guo, Hong; Wang, Dongwen (Frontiers in Immunology, 2025)
Prostate-Specific Membrane Antigen (PSMA) is a highly expressed and structurally unique target specific to prostate cancer (PCa). Diagnostic and therapeutic approaches in nuclear medicine, coupling PSMA ligands with radionuclides, have shown significant clinical success. PSMA-PET/CT effectively identifies tumors and metastatic lymph nodes for imaging purposes, while 177Lu-PSMA-617 (Pluvicto) has received FDA approval for treating metastatic castration-resistant PCa (mCRPC). Despite their success, radionuclide-based diagnostic and therapeutic methods face limitations such as high costs and significant side effects. Recently, near-infrared (NIR) fluorescence imaging and phototherapy have advanced significantly in biomedical applications. It’s benefits, such as deep tissue penetration, real-time precision, and minimal side effects, have driven broader clinical adoption, especially in fluorescence-guided surgery (FGS). This review suggests combining NIR dyes with PSMA ligands to enable targeted, high-resolution imaging with superior signal-to-background ratios, facilitating precise FGS. NIR techniques can also aid pathological diagnosis in ex vivo specimens. Furthermore, combining photosensitizers with PSMA ligands allows localized photothermal (PTT) or photodynamic therapy (PDT) under NIR irradiation, producing heat or reactive oxygen species (ROS) to treat PCa. This review aims to extend the clinical success of radionuclide-based PSMA targeting by exploring advances in NIR-based FGS and phototherapy, presenting a promising new diagnostic and therapeutic approach.